ADAPTATION AND VALIDATION OF THE INDONESIAN VERSION OF THE HEALTH BELIEF MODEL INSTRUMENT FOR PARENTS - Eka Wuri Handayani; Fredrick Dermawan Purba; Dyah Aryani Perwitasari (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Children are a crucial population requiring COVID-19 vaccination. With the global rollout of COVID-19 vaccines, the increasing number of unvaccinated children and adolescents has raised concerns. To was translated, adapted, and validate the Health Belief Model instrument for parents of children aged 6–11 years regarding COVID-19 vaccination in the Indonesian language. Cross-cultural translation and adaptation were conducted according to international standards. The instrument testing process, according to Beaton et al., (2020), involves five stages: forward translation, synthesis of the translation results, back translation, review of the back translation, and readability testing. Respondents were purposively selected from the parents of children aged 6–11 years. Face and content validity were achieved for the Indonesian version of Health Belief Model for parents of children aged 6–11 years. The validity of each statement item was assessed using Pearson Correlation with a significance level of 0.05 and 193 respondents, resulting in an r table value of 0.1406. The constructs within the Health Belief Model were deemed valid based on the Pearson Correlation values, as the coefficient values were greater than the r-table value (r > 0.1406; p < 0.05). The constructs in the Health Belief Model were also reliable, with a Cronbach’s alpha value of 0.657. The culturally adapted Indonesian version of the Health Belief Model instrument for parents of children aged 6–11 years regarding COVID-19 vaccination is considered valid and reliable for use in research among the parent population of children aged 6–11 years in the context of COVID-19 vaccination.